Testing the sensitivity of past climates to the indirect effects of dust. Issue 11 (12th June 2017) - Sagoo, Navjit; Storelvmo, Trude
Abstract: Mineral dust particles are important ice nuclei (IN) and as such indirectly impact Earth's radiative balance via the properties of cold clouds. Using the Community Earth System Model version 1.0.6, and Community Atmosphere Model version 5.1, and a new empirical parameterization for ice nucleation on dust particles, we investigate the radiative forcing induced by dust IN for different dust loadings. Dust emissions are representative of global conditions for the Last Glacial Maximum and the mid‐Pliocene Warm Period. Increased dust leads to smaller and more numerous ice crystals in mixed phase clouds, impacting cloud opacity, lifetime, and precipitation. This increases the shortwave cloud radiative forcing, resulting in significant surface temperature cooling and polar amplification—which is underestimated in existing studies relative to paleoclimate archives. Large hydrological changes occur and are linked to an enhanced dynamical response. We conclude that dust indirect effects could potentially have a significant impact on the model‐data mismatch that exists for paleoclimates. Plain Language Summary: Mineral dust and climate are closely linked, with large fluctuations in dust deposition recorded in geological archives. Dusty conditions are generally associated with cold, glacial periods and low dust with warmer climates. The direct effects of dust on the climate (absorbing and reflecting radiation) are well understood; however, the indirect effects of dust on climate have been overlooked. Dust indirectly impacts the climate through its role as ice nuclei; the presence of dust makes it easier for ice to form in a cloud. We explore the indirect effects of dust in climates with different dust loading from the present by conducting a climate modeling study in which dust are able to act as ice nuclei. Including dust indirect effects increases the sensitivity of our model to changes in dust emission. Increasing dust impacts ice crystal numbers (increased) and size (reduced) in a cloud. This increases cloud reflectivity and lifetime, which increases the sunlight reflected by the cloud and cools the climate. Including the indirect effects of dust has a large impact on the climate, and our results indicate that this is an important but overlooked aspect of paleoclimates that could remedy some of the existing shortcomings of paleoclimate simulations. Key Points: Model sensitivity to modified dust emissions is amplified with the inclusion of a more realistic ice nucleation scheme in which dust act as ice nuclei Modifying dust emissions affects cloud microphysical and macrophysical properties, cloud radiative forcing, temperature, polar amplification, and hydrology Dust indirect effects have a significant climate impact, and their inclusion may improve deficiencies between existing paleoclimate simulations and archives